Analysis of the ball speed in the kick of futsal players as a function of the contact instep of the lower limbs (Research, Society and Development, 2022)
In order to identify the variation of the ball speed in kicks performed with different contact faces in futsal, 30 athletes were evaluated, who performed three kicks with the inside face, back and toe, of the 10-meter shot, separating the dominant and non-dominant sides. A BUSHNELL speed radar, model 101911, measuring in km/h was used. Statistical tests were performed and the results showed statistical differences in toe and instep kicks, with velocity greater than the inner instep in both dominant and non-dominant. These findings help in training planning, with the aim of increasing the effectiveness of this motor action.